Exploring cross-cultural psychology: Exercises for instructors and students - Devonis, David C. (New York, USA: Routledge, 2024)
"Exploring Cross-Cultural Psychology is an accessible text that provides material for generating interactive discussion of a broad sampling of topics in cross-cultural psychology"--
Includes bibliographical references and index.
Keywords: Ethnopsychology; Social Psychology